2015
DOI: 10.1186/s13028-016-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of Coxiella burnetii at the wildlife–livestock interface in the Eastern Pyrenees, Spain

Abstract: Background Coxiella burnetii is a zoonotic bacterium that infects a wide range of animal species and causes the disease Q fever. Both wild and domestic ruminants may be relevant in the epidemiology of C. burnetii infection. In order to investigate the significance of the ruminant host community in the alpine and subalpine ecosystems of the Eastern Pyrenees, Northeastern Spain, in the epidemiology of Q fever, a serological survey was performed on samples from 599 wild and 353 sympatric domestic ruminants.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Infected horses, mules and donkeys in rare cases can abort . C. burnetii shedding has been described in many species of wild animals commonly encountered on farms, including wild migratory and nonmigratory birds . Methods to reduce risk from these species, particularly those that are reproductively active, have not been shown yet to be effective; however, it might be prudent to restrict their access to livestock whenever feasible …”
Section: Control Of Coxiellosismentioning
confidence: 99%
“…Infected horses, mules and donkeys in rare cases can abort . C. burnetii shedding has been described in many species of wild animals commonly encountered on farms, including wild migratory and nonmigratory birds . Methods to reduce risk from these species, particularly those that are reproductively active, have not been shown yet to be effective; however, it might be prudent to restrict their access to livestock whenever feasible …”
Section: Control Of Coxiellosismentioning
confidence: 99%
“…from 9.8% in the Basque country (northern country) to *30% in the islands of Canarias, considered a highly endemic region(Garcı ´a-Pe ´rez et al 2009, Rodriguez et al 2010, Ruiz-Fons et al 2010, Ferna ´ndez-Aguilar et al 2016, Bolan ˜os-Rivero et al 2017. In fact seroprevalence in sheep is estimated to be around 15-20% in many countries of the world(Guatteo et al 2011), which confirms that sheep of Portugal showed relatively low Q fever seroprevalence.When comparing anti-C. burnetii presence in sheep according to NUTS II distribution, a higher seroprevalence in the Center region can be observed when comparing to the other regions of Portugal.…”
mentioning
confidence: 99%
“…The kit selected for this study (IDEXX Q-Fever [Coxiella burnetii] Antibody Test Kit, Idexx Laboratories, Rydalmere, NSW, Australia) is validated for ruminants, 32,33 but has previously been used for the detection of antibodies in deer sera. [22][23][24] 96-well plate, positive and negative controls were assayed in duplicate and the mean optical density (OD) of each was used for calculations.…”
Section: Sample Sourcesmentioning
confidence: 99%
“…The IDEXX ELISA was selected over other commercial ELISA kits on the market as reports exist in the literature of its successful use with cervid samples. [22][23][24] Furthermore, one such study demonstrated binding of IgG from Korean water deer to the anti-ruminant IgG in the IDEXX ELISA Chekit Q Fever kit. 24 Considering this and the lack of validated tests for wild species, the use of commercial kits for closely related species is justifiable.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation